A Method of Well-Spread Pachytene Chromosome Preparations for Plant Species with Large Genomes Suitable for the Immunolocalization of Meiotic Proteins - Natalya Kudryavtseva; Aleksey Ermolaev; Ludmila Khrustaleva (Methods and Protocols)
Well-spread pachytene chromosomes are critical for studying the location of meiotic proteins along individual chromosomes. However, producing good spreads in species with large genomes is challenging due to the tangling of pachytene chromosomes. Existing protocols often fail to achieve proper separation of large chromosomes in spreads. Here, we describe in detail an improved protocol that ensures the effective separation of large pachytene chromosomes and demonstrates its suitability for protein immunodetection. To develop the protocol, pollen mother cells at the middle–late pachytene stage from Allium fistulosum, a species with a large genome and chromosomes, were used. The protocol involved three main steps: fixing anthers in Clark’s solution (ethanol–acetic acid, 3:1), digestion in an enzyme mixture, and gentle squashing in 45% acetic acid. A clear ZYP1 signal on all separated chromosomes was observed. The high quality of well-spread pachytene chromosomes obtained with the modified protocol allowed for the easy extraction of individual chromosomes for more precise detection and analysis of the proteins of interest.